The effect of time served on recidivism: An interdisciplinary theory - Orsagh, Thomas J. (Journal of quantitative criminology, 1988)
The research reported in this paper is concerned with the functional relation between the probability that an individual offender will recidivate and the time that the offender has served in prison as a consequence of the offense. Theory suggests that time served affects recidivism through both specific deterrent and social bonding effects. The former is hypothesized to produce an inverse relation between recidivism and time served; the latter, a direct relation. The paper reviews the literature concerning these two theoretical relations. The review provides the basis for the establishment of a multiequation model whose principal result is to suggest that, more than likely, the recidivism/time served relation is a U-shaped function. The empirical model used to evaluate the hypothesis that the function is U-shaped uses the occurrence of a new arrest as its dependent variable. The model is estimated using OLS and LOGIT procedures. The data used for estimation relate to 1425 prisoners released from the North Carolina prison system in 1980. Recidivistic outcomes are measured at the end of the first and second years subsequent to their release. The research is unique in that it represents the first effort to synthesize the economist's specific deterrence model with the sociologist's social bonding model. The theory provides an explanation for the failure of past empirical work to establish a relation between time served and recidivism. The research is also unique in its a priori assumption of a U-shaped behavioral relation and its attempt to measure that particular relation. The data support the hypothesis that time served affects postprison recidivism rates and that the direction of the effect varies by offense class.